Ethnic Diversity and Firms' Export Behavior - Pierpaolo Parrotta; Dario Pozzoli; Davide Sala (Institute for the Study of Labor (IZA), 2014)
Selling internationally requires products that resonate with an international customer base and therefore an approach to markets that is in keeping with diverse cultures (i.e., relational capital). As emphasized by international business studies, this relational capital is in turn related to the successful teaming of a diverse workforce, as this process teaches employees to operate in multicultural environments. This knowledge becomes like an intangible asset to which firms can resort, also when engaging in international transactions. We explore this channel empirically, investigating the impact of workforce diversity on firms' exporting performances and find that ethnic diversity further justifies firms' different presence in international markets. Since hiring is not a random practice, and firms ultimately select into ethnically different labor forces, we exploit the EU enlargement of 2004 to instrument for the diversity of the pool of workers locally recruitable. Because migrants tend to settle where the attitude toward them is most favorable, we use the median voter's political ideology at firm's location to measure the hostility at time of settlement. This gives our instrument spatial variation besides time variation.
Keywords: J15; F14; F15; F16; D22; 330; ethnic diversity; export; EU enlargement; median-voter ideology